An analysis of the financing mechanisms proposed for funding national health insurance in South Africa - Stevens, Nicol Susan (Rhodes University, Faculty of Commerce, Department of Accounting, 2012)
In the 2011 Budget Speech, the Minister of Finance announced that South Africa would be introducing National Health Insurance. The Minister described the financing mechanisms under consideration for funding National Health Insurance. The Minister also referred to eight countries, namely Japan, South Korea, Taiwan, Chile, Colombia, Mexico, Thailand and Vietnam as examples of countries which had successfully implemented universal health coverage. These countries were selected for the purpose of the present research. The goal of this study was to analyse the health care financing mechanisms under consideration in South Africa to determine if they were in line with international trends and "best practice" in relation to South Africa's economic profile. To determine whether the economic situation in South Africa is comparable to the eight countries selected for the research, a high-level comparison was made of the economic profile of South Africa and the eight countries, based on certain demographic, macro-economic, health expenditure and health status indicators. The health care financing mechanisms used in the eight countries was also analysed. International trends suggested that health care should be financed primarily through pre-payment systems, that financing mechanisms should preferably be progressive in nature and that a large share of funding should be from government sources (albeit shared between general tax revenue and specific health care contributions). The financing mechanisms under consideration in South Africa reflect these norms. The health systems in the eight countries analysed all exhibited elements of "good performance" and also complied, to a large extent, with international trends, but the frnancing models used for funding health care in the eight countries were country-specific and could therefore not be compared directly or used to recommend a system for South Africa. Areas not addressed by this thesis include the implications of a centralised healthcare system, the implications of a single-payer system, the benefit package to be offered and its cost implications, the role of private healthcare providers and how the significant human resource scarcity and infrastructure backlogs will be addressed.
Keywords: Uncatalogued